Optically Sensing for Thyroid Profile Hormones in Blood (Medico Legal Update, 2021)
Optical biosensors present great characteristics compared to traditional analytical techniques because theyallow direct, realistic, and label-free detection of many biological and chemical materials. Thyroid hormonesare created by the thyroid gland, which is found in the abdomen of the thyroid cartilage Thyroid hormonegoverns metabolic processes necessary for normal outgrowth and evolution in addition to regulatingmetabolism in adults. It is established that the condition of the thyroid hormone is related to body weight andenergy disbursement. This work using a single-mode tapered fiber biosensor to detect changes in the levelof thyroid hormone by measurement of the intensity changing with the concentration of hormone by using adiode laser (450 nm) wavelength as an optical source, the single-mode tapered fiber as the sensor connectedwith ocean (HR 2000) spectrum analyzer by an adapter and finally connected to the pc to show the result.The lowest intensity of transmitted light recorded with a higher concentration of the hormone because of thehigh matching and specific selection of laser wavelength with the structure of the thyroid hormone in whichgive the specific amount of the hormone present in the sample. Thyroid hormone can be detected by using alaser biosensor. The higher concentration of thyroid hormone referred to the lowest intensity of light.